Cover Feature: Aptamers for SARS‐CoV‐2: Isolation, Characterization, and Diagnostic and Therapeutic Developments (Anal. Sens. 5/2022). Issue 5 (7th June 2022) - Amini, Ryan; Zhang, Zijie; Li, Jiuxing; Gu, Jimmy; Brennan, John D.; Li, Yingfu
Abstract : The cover feature image shows nucleic acid aptamers armed and ready for our battle against the monstrous SARS‐CoV‐2 virus. Often thought of as "chemical antibodies", these molecular recognition elements are equipped with several unique benefits and have thus been a popular research subject worldwide. Many aptamers for recognizing the spike and nucleocapsid proteins of SARS‐CoV‐2 have been developed and examined as diagnostic and therapeutic weaponry for the war against COVID‐19 and future pandemics. More information can be found in the Review by J. D. Brennan, Y. Li, and co‐workers .